DETERMINAN AKSESIBILITAS PANGAN DI SUMATERA: Pendekatan Simulasi Kebijakan - Teapon, Rizal Rahman H; Evalia, Nur Afni (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The main objective of this research is to analyse the impact of government spending, especially social assistance and the food security budget, on food accessibility in Sumatra. This research uses secondary time series data for the 2010-2019 period. The cross section data consists of 10 provinces, namely, Aceh, North Sumatra, West Sumatra, South Sumatra, Riau Islands, Riau, Bengkulu, Jambi, Lampung and Bangka Belitung. The research data source was obtained from the Food Security Agency of the Ministry of Agriculture of the Republic. This research uses a system of simultaneous equations including 5 equations, consisting of 3 structural equations and 2 identity equations. Simultaneous equation regression results for food accessibility show that increasing consumption of rice and corn can reduce the prevalence of inadequate food consumption in Sumatra. On the other hand, the increase in the prevalence of inadequate food consumption was caused by an increase in malnutrition and an increase in the prevalence of inadequate food consumption in year t-1. The research results also show that an increase in the prevalence of inadequate food consumption in year t-1, an increase in the percentage of the population with malnutrition and an increase in poverty in year t-1 have an effect on increasing poverty. The increase in regional economic growth in the food crop sub-sector (increased food accessibility) is driven from the production, consumption side and the influence of the increase in regional economic growth in the food crop sub-sector in previous years (t-1). The simulation results show that social assistance and the government's food security budget contribute to increasing regional macroeconomic variables such as regional economic growth in the food crop sub-sector, per capita income and AHK's gross regional domestic product.